Who is responsible for the shift to a more sustainable society? : how politicians view responsibility and accountability for environmental problems - Larson, Rebecca (SLU/Dept. of Urban and Rural Development, 2019)
Climate change is one of the biggest challenges of our time. Lately, an increased demand that politicians need to act stronger and faster in the fight against climate change has been heard from the public. At the same time, responsibility and accountability for the climate change question remain unclear, as well as what role different actors in society and politics should have in solving environmental problems. Politicians represent a group in society that has been given power by the public to make political decisions. This study aims to gain an understanding, from the point of view of elected politicians, of who they think is responsible in the shift to a more sustainable society. To reach the aim of this study, I have conducted nine semi-structured interviews with Swedish politicians. Using Carol Bacchi’s “What’s the problem represented to be?” (WPR) approach, the study looks at how politicians represent the problem of climate change through the solutions put forth, and who is seen as responsible. Furthermore, the study looks at how the respondents view their role in solving environmental problems. The findings offer insights to how climate change is looked upon from the point of view of politicians and sheds light on the complex issue of responsibility and accountability in the shift to a more sustainable society.